Climate change impacts on hydropower generation at Kenyir Lake - Azreen Harina, Azman; Nurul Nadrah Aqilah, Tukimat; Male, M.A. (School of Engineering, Taylor's University, 2021)
Climate change is triggered by human activities that produce greenhouse gas emissions and affect people in various ways. It is crucial to study the severity of rainfall in the certain potential areas that exposed to hydro-meteorological disasters in climatic trends transition. The objectives of the study are to evaluate the severity of rainfall trends and also to predict the fluctuations of hydropower generation in Kenyir Lake triggered by the variations of climatic factors under selected Representative Concentration Pathways, RCPs (RCP2.6, RCP4.5 and RCP8.5) suggested in the Intergovernmental Panel on Climate Change’s (IPCC) fifth assessment report. The historical daily data of seven rainfall stations for 30 years’ period (1988 - 2017) and global climate model data for RCP2.6, RCP4.5 and RCP8.5 also for 30 years’ period (2041-2070) were used. The statistical downscaling model (SDSM) was used to analyse the data. The predicted rainfall data from 2041 to 2070 then compared with the base period rainfall (1988-2017). Kenyir Lake received highest amount of rainfall in November to January during north-east monsoon. The significance differences were recorded in November and December where abrupt fall of rainfall distribution predicted to happen for all RCPs. The results proved that the higher emissions level will give the more effect to the climate trend as previous researcher found that warming will remain beyond 2100 for all RCP scenarios except RCP2.6. The lowest generated value at Kenyir is in 1997 and the highest value is in 2017. The increment of NUG clearly happens in 10 years’ interval where there was 78.67% of increment in 2007 compared to 1997. There is an increase that occurs although there are fluctuations every year. Increases in temperature because of climate change effects will increase the energy demand. Rising temperatures gives the varies patterns of demand because higher temperature will create higher cooling demand. Besides that, power generation can change accordingly by the decreasing stream flow and increasing water temperature. It shows that climate change tremendously affects the energy demand patterns and supply systems.